Custo do capital divisional em empresas multinacionais: aplicação de metodologia - Manetti, Luiz Fernando (2005)
This work aims to analyze the adoption of a divisional cost of capital in multinational companies and its reflexes in the project evaluation under the shareholders perspective, been based in the risk and return context. Aiming to simplify the process of project analysis, it is usual that the multinational companies adopt a single corporate cost of capital for all its divisions, and all the new projects are evaluated, rejected or accepted, taking into account this corporate cost of capital. In order to analyze some implications of this simplification, this work will apply an existent methodology to determine the different opportunity costs of each division, and furthermore it will analyze the comparative impact between the corporate cost of capital and the divisional cost of capital, under the perspective of the shareholder. This work will show that when the divisions of a multinational company present a cost of capital that is too much different from each other, or too much different from the corporate cost of capital adopted, the use of divisional costs of capital represents a leap in terms of the incorporation of the risk concept, increasing and improving the project analysis, keeping a reasonable level of simplicity but generating more value to the shareholder.